Advances in Nanomaterials Fundamentals, Properties and Applications (Springer International Publishing, 2018)
This exploratory textbook starts with fundamentals that satisfy the needs of a diverse group of educators, researchers and students aspiring to engage in research and engineering of nanomaterials. It bridges the gap between undergraduate students in science and engineering who have not yet chosen a specific career path, graduate students still considering different disciplines and the cross-cutting scientific topics in nanomaterials. It extends to methods of common practice in the field, spanning experimental, and theoretical techniques. The extensive use of nanomaterials, such as carbon nanotubes, in the future of global technological solutions underscores the relevance of this text aimed at students and researchers with a range of interests. "Advances in Nanomaterials: Fundamentals, Properties and Applications," is ideal for senior undergraduate and graduate students, faculty and general science enthusiasts interested in nanomaterials across contexts ranging from solar energy, structural engineering, to medical devices, to semiconductors. Guides readers from the fundamental principles of science required as background knowledge for nanomaterials; Enriches readers with the latest developments from research on nanomaterials; Introduces readers to common jargon with simplified explanation and illustrations, enabling them to follow state-of-the-art advances published in the archival literature; Provides a thorough overview of common nanomaterial synthesis, characterization and measurement methods, making the text a good reference for advanced undergraduate and graduate students; Includes practical examples, references and future perspectives to familiarize readers with challenges and trade-offs encountered in actual R&D.